Typification of two names in the genus Hordeum (Poaceae, Triticeae) - Ferrer-Gallego, P. Pablo; Fabado, Javier (Phytotaxa, 2022)
The typification of the name Hordeum marinum Hudson (Poaceae) is discussed. The name is lectotypified using an original illustration from Morison’s Plantarum historiae universalis Oxoniensis, and an epitype is also selected. The type of the name H. gussoneanum is also discussed, and a specimen preserved at FI is designated as second step lectotype.